2008
DOI: 10.1186/1471-2105-9-425
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of dominant and dormant genes from expression data using a novel generalization of SNR for multi-class problems

Abstract: Background: The Signal-to-Noise-Ratio (SNR) is often used for identification of biomarkers for two-class problems and no formal and useful generalization of SNR is available for multiclass problems. We propose innovative generalizations of SNR for multiclass cancer discrimination through introduction of two indices, Gene Dominant Index and Gene Dormant Index (GDIs). These two indices lead to the concepts of dominant and dormant genes with biological significance. We use these indices to develop methodologies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Similarly for RHAB tumour class D63878_at, X54673_at genes are reported in Pomeroy et al (2002). In literature (Pomeroy et al, 2002;Tsai et al, 2008), D85418_at, D30755_at and D31888_at genes are reported to belong to NCER class as we obtained in our work. Gene U79288_at is reported in Tsai et al (008) to belong to PNET class.…”
Section: Gene Markers For Brain Tumour Datasetsupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly for RHAB tumour class D63878_at, X54673_at genes are reported in Pomeroy et al (2002). In literature (Pomeroy et al, 2002;Tsai et al, 2008), D85418_at, D30755_at and D31888_at genes are reported to belong to NCER class as we obtained in our work. Gene U79288_at is reported in Tsai et al (008) to belong to PNET class.…”
Section: Gene Markers For Brain Tumour Datasetsupporting
confidence: 66%
“…Gene U79288_at is reported in Tsai et al (008) to belong to PNET class. Z31560_s and U50648_s_at genes are reported to belong to MD class in Wang et al (2008) and Tsai et al (2008), respectively. These findings are similar to the observations derived from our present study.…”
Section: Gene Markers For Brain Tumour Datasetmentioning
confidence: 99%
“…In [13] Y.-S. Tsai presents an innovative generalizations of SNR for multiclass cancer discrimination is proposed through the beginning of two indices, one is called Gene Dominant Index and another one is called Gene Dormant Index (GDIs) . These two indices lead to the concepts of dominant and dormant genes with biological significance.…”
Section: Generalization Approachmentioning
confidence: 99%
“…Tsai et al [13] Propose an innovative generalizations of SNR for multiclass cancer discrimination is proposed through the beginning of two indices, one is called Gene Dominant Index and another one is called Gene Dormant Index (GDIs).…”
Section: Redundancy Removalmentioning
confidence: 99%
“…A centroid-based ranking score was proposed as a multiplication of the difference between class and overall mean, with the disparity between between-class sum of squares to withinclass sum of squares [11]. A generalization of signal-to-noise ratio for multiclass gene selection was developed by defining gene dominant index and gene dormant index [12]. Final classification was thus performed using a few top-ranked dominant and dormant genes.…”
Section: Introductionmentioning
confidence: 99%